Transformations in the Ownership Structure of Credit Unions: Banking Service Rates and the Expectations of Members and Directors - Bruno José Canassa; Davi Rogério de Moura Costa; Carlos Alberto Grespan Bonacim (BBR: Brazilian Business Review)
Open membership and mergers are common transformations in the ownership structure in Brazilian credit unions. Following the logic that they are motivated by the expectations of members and directors, this study associates these transformations with the banking services rates offered by credit unions. We employ ordered and multinomial logit models to investigate whether abnormal positive bank spreads-reflecting rates that could offer few advantages to members and large private benefits to directors-increase the probability of transformation. Our results indicate that the expectations of members and directors explain credit unions’ transformation, as seen in size and performance. The evidence reinforces that, under expectations of gains, members and directors play an active role in the decision to transform the ownership structure of credit unions, suggesting improvements in the corporate governance and incentives for mergers so that credit unions can grow to benefit members.